Penerapan Algoritma Boldy Vigna Untuk Mengkompresi Pada File Audio Aplikasi Kajian Dan Murottal Islami - Lobe Lahmuddin (Management of Information System Journal, 2022)
At this time mobile phones have developed into a means to study a subject matter in different spheres of life with a wider scope, one of which can make it easier for everyone to access various fields of knowledge without exception, even in the field of religion, now it can be accessed with a Islamic Studies and Murottal applications that are widespread in the play store.The Murottal Isalami Study Application is an application with a clear study delivery technique. However, in the Islamic study and murottal application there are 192 audio studies with the length of the audio duration, which also affects the storage capacity which will also increase. No wonder most Islamic studies and murottal applications have a large capacity so it will require a lot of space to store the application files.This can be avoided if the application's audio file goes through the compression process first. One of the methods used in compressing or compressing data is the Boldy Vigna algorithm. The Boldy vigna algorithm sorts the most appearing characters to the smallest bit and the rare characters to the largest bit. That way, the file size can be minimized from the original size..